The cicada’s song as a reminder of (in)mortality in haiku and Greek epigram - Sánchez i Bernet, Andrea (Mirai. Estudios Japoneses, 2025)
Haiku is characterized by its syncretism in describing everyday scenes and by its attention to seemingly insignificant details and small beings such as insects. The present work aims to explore, specifically, the significance of the cicada as a recurring motif in haiku. First, some of the most representative haiku from different periods where this animal appears are compilated and then its different meanings and associations are systematized. Secondly, a comparison is proposed with the cicada in the Greek epigram, a genre with formal and aesthetic similarities, in order to clarify, from a contrastive and intercultural perspective, what is the specific role of the cicada in these Japanese compositions. Although both traditions observe the same characteristics of this small animal –its summer seasonality, its use as children's entertainment and its loud song–, Greek poetry takes it as a symbol of immortality with clearly positive connotations, while in haiku these considerations are less frequent and the same traits are more often interpreted as a melancholic reminder of the ephemeral nature of life.
Keywords: cicada; haiku; epigram; literary mortif; mono-no aware